The loess formation of kansas - Freeman, Joanna (My University, 1896)
Introduction: The picture is beautiful, but not always the same! Love for the picture grows with our growth, and ideas change with better acquaintance. Look at the picture. Some shaded vale, clothed with the harmonious color of nature; dancing water sparkling and flashing here and there through the green, a rugged hill beyond giving strength and majesty, and an atmosphere of complete rest pervading all. Thus may nature come – love in her look, and strength in her mien; or she may appear in a garb, rough, sharp-angled, so strong and mighty in appearance, so grand she awes us. Still she draws us nearer, she invites better acquaintance, and leads us on and on, yet only giving glimpses of the great past, and of the eternal future. But prove the depth of the past, and the grandeur of the future which we feel is to come, she inspires better labor, higher aspirations, and sends enthusiasm which conquers all obstacles.
Citation: Freeman, Joanna. The loess formation of kansas. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Vale; Rugged hill; Kansas; Theses; Manuscripts (documents)